Can Students' Scientific Literacy and Critical Thinking Skills be Improved through the Development of Science Teaching Materials with a STEM-integrated Project Based Learning (PjBL) Model? (A Systematic Review) - Susilawati; Ahmad Harjono; Ainun Sabrina; Syarful Annam (Jurnal Penelitian Pendidikan IPA, 2025)
In an era where innovation and problem-solving are central to scientific and technological advancement, education must equip students with the necessary skills to navigate complex challenges. Science literacy and critical thinking have become pivotal competencies in the 21st century. Integrating STEM (Science, Technology, Engineering, and Mathematics) into Project-Based Learning (PjBL) has emerged as a promising pedagogical strategy to nurture these skills. This research aims to identify and analyze research trends of STEM-integrated PjBL model to improve students' science literacy and critical thinking skills. This research method is descriptive and analytical. The data used in this research was obtained from documents indexed by Google Scholar from 2016-2025 using Publish or Perish and Dimension.ai. Research procedures use PRISMA guidelines. The data identified and analyzed are the type of publication, publication source, and the title of research abaout the topic that is widely cited. The data analysis method uses bibliometric analysis assisted by VOS viewer software. The results of the analysis show that research trend on STEM-integrated PjBL model to improve students' science literacy and critical thinking skills indexed by Google Scholar from 2016 to 2025 has experienced a fluctuating increase. There are many documents in the form of articles, proceedings, chapters and preprints that discuss research into the STEM-integrated PjBL model to improve students' science literacy and critical thinking skills. Key words that are often used in research about it are systematic literature review, implementation, development, meta analysis, etc.